3D ultrasonic signal compression algorithms for high signal fidelity - Govindan, Pramod; Gonnot, Thomas; Gilliland, Spenser; Saniie, Jafar (2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS), 2013)
Ultrasonic signal processing applications require huge amounts of data to be processed. Further, high computational performance is essential to meet the real-time requirements. Compression of the signal helps to reduce the data size and storage requirements as well as allow for rapid transmission of data to remote locations. High signal fidelity is significant in many of practical applications like ultrasound medical imaging and nondestructive testing. In this study, we discuss two methods for ultrasonic signal compression which offer high signal fidelity - Discrete Wavelet Transform and signal decimation with the Nyquist rate limit. The compression algorithm is implemented on a reconfigurable system-on-chip platform using programmable hardware logic as well as in software using an embedded processor. The implementation details and the performance of the compression algorithms on both the hardware and software are analyzed in this paper.